How managerial view the dividend policy: A case of UAE - Farhan Basheer, Muhammad; Abdullah Ahmad, Aref; Ghulam Hassan, Saira (Opción, 2019)
The pre-eminent objective of the current research is to highlight the managerial view regarding the factors which affect the managerial decisions regarding the formulation of dividend policy. For this purpose, we have surveyed the managers of non-financial firms listed with Dubai financial markets. Moreover, we are also interested in highlighting that how managerial perception about the importance of these factors varies from country to country. Our next objective is to know the level of importance, managers of firms listed in Dubai financial market give to dividend processes and pattern, firm value. dividend policy and residual dividend policy. Finally, we are interested in measuring the level of support that managers of firms listed in the Dubai financial market give various explanations for paying dividends. The study has used a mail survey of managers of firms listed in the Dubai financial market that have paid at least one cash dividend during the period of 2015-2017 as a primary means of collecting data. No single pattern in rankings of factors among different countries has emerged. However, like their American, Canadian and Indonesian occupational fellows, managers of firms listed in Dubai financial market ranked, F3 (level of current earnings), F2 (pattern of past dividends), F1 (Stability of earnings) at the top. According to Managers of firms listed in the Dubai financial market, dividend decisions have a significant effect on firm value. Meanwhile, they have shown a great deal of support with all dividend theories, but most strong agreements are given to clientele and agency theory. In spite of a high response rate of almost 66.7 percent, the number of responses received has limited our ability to test statistically significant or insignificant difference among different industrial and firm characteristics.